2018
DOI: 10.1093/cid/ciy654
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2a Safety, Pharmacokinetics, and Acceptability of Dapivirine Vaginal Rings in US Postmenopausal Women

Abstract: See the Major Articles by Liu et al on pages 1129-35 and Hoesley et al on pages 1136-43.) Background. Postmenopausal women have unique sociobiological human immunodeficiency virus (HIV) risks. We evaluated the safety, pharmacokinetics, and acceptability of a microbicide dapivirine (DPV) vaginal ring (VR) versus placebo in postmenopausal women. Methods. We enrolled 96 HIV-negative postmenopausal US women in a phase 2a double-blind, randomized (3:1) trial of monthly VRs containing 25 mg DPV or placebo used conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…DPV was quantified in plasma and cervical tissue using previously described, liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) by the Clinical Pharmacology Analytical Laboratory at the Johns Hopkins University School of Medicine [24,25]. A modified version of a previously published LC‐MS method, which employed CVF extraction from Dacron swabs via a 1:1 solution of methanol:water, was used for DPV quantitation in CVF [26].…”
Section: Methodsmentioning
confidence: 99%
“…DPV was quantified in plasma and cervical tissue using previously described, liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) by the Clinical Pharmacology Analytical Laboratory at the Johns Hopkins University School of Medicine [24,25]. A modified version of a previously published LC‐MS method, which employed CVF extraction from Dacron swabs via a 1:1 solution of methanol:water, was used for DPV quantitation in CVF [26].…”
Section: Methodsmentioning
confidence: 99%
“…The differences correlated with reduced adherence in younger women. Safety assessment, PK and acceptability of the DPV vaginal ring [37] confirmed its therapeutic potential. DPV plasma levels were also comparable in all enrolled women.…”
Section: Implantablesmentioning
confidence: 78%
“…Vaginal rings, well known for their use as birth control devices, are also being evaluated for extended ARV release [33][34][35][36][37][38]. Drugs used in rings are stabilized in either polymeric matrices or cores [33,34,36,39].…”
Section: Implantablesmentioning
confidence: 99%
“…Many of the advances in ring design and technology during the last twenty years have been driven by concerted global efforts to develop new antiretroviral-releasing ring products for preventing sexual transmission of HIV infection in women ( Vincent et al, 2018 ; Keller et al, 2019 ; Baum et al, 2015 ; Kiser et al, 2012 ; Woolfson et al, 2006 ; Malcolm et al, 2005 ; Baeten et al, 2020 ; Malcolm et al, 2016 ; Malcolm et al, 2014 ; van der Straten et al, 2016 ; Malcolm et al, 2010 ; Spence et al, 2015 ; Malcolm et al, 2012 ; Thurman et al, 2013 ). A matrix-type silicone elastomer vaginal ring providing sustained release of the antiretroviral drug dapivirine (DPV) – a potent non-nucleoside reverse transcriptase inhibitor – was developed by the International Partnership for Microbicides (IPM) to offer women a self-initiated, long-acting HIV prevention option ( Devlin et al, 2013 ; Nel et al, 2009 ; Nel et al, 2016a ; Baeten et al, 2016 ; McCoy et al, 2017 ; Nel et al, 2014 ; Chen et al, 2019 ; Bunge et al, 2020 ). In two Phase III safety and efficacy trials, the 25 mg DPV ring was shown to reduce the risk of HIV acquisition in women compared to a placebo ring ( Nel et al, 2016a ; Baeten et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%